Mixed jurisdictions worldwide : the third legal family - Palmer, Vernon V. (Cambridge : Cambridge University Press, 2012)
'This examination of the mixed jurisdiction experience makes use of an innovative cross-comparative methodology to provide a wealth of detail on each of the nine countries studied. It identifies the deep resemblances and salient traits of this legal family, and the broad analytical overview highlights the family links while providing a detailed individual treatment of each country which reveals their individual personalities.
This updated second edition includes two new countries (Botswana and Malta), and the appendices explore all other mixed jurisdictions and contain a special report on Cameroon.'--pub. desc.
A descriptive and comparative overview / Vernon Valentine Palmer -- The Republic of South Africa / C.G. van der Merwe, Jacques du Plessis, Marius de Waal, Reinhard Zimmermann, and Paul Farlam -- Scotland / Elspeth Reid -- Louisiana / Vernon Valentine Palmer and Harry Borowski -- Quebec / Michael McAuley -- Puerto Rico / Luis Muniz-Arguelles -- The Philippines / Pacifico Agabin -- Botswana / Charles Fombad -- Malta / Biagio Ando, Kevin Aquilina, J. Scerri-Diacono, and David Zammit -- Israel / Tamar Gidron.
Includes bibliographical references and index.
Keywords: Civil law systems; Common law; Legal polycentricity